The Effects of Nitrogen, Potassium and Chicken Dung on Yield and Quality of Chilli (Capsicum Annuum L.) Grown on a Bris Soil - Ariffin, Zaharah (1989)
Field experiments were conducted to determine the requirements of N, K and chicken dung for chilli (Capsicumannuum L.) grown on abris sandy soil . The treatments that were evaluated comprised three levels of N (100, 200 and 300 kg N/ha), three levels of K (100, 200 and 300 kg K/ha) and two levels of chicken dung (0 and 10 t/ha). The study was conducted for two consecutive cropping seasons. There were difference sin crop response pattern for the two cropping seasons. In the first crop, response to N was linearly significant only for fruit number and N, P and K contents in the leaf and P contents in the fruit. In contras t response to N in the second crop was obtained for yield, fruit number, fruit weight, N and Ca contents in the fruit and N, K.